(untitled) (Annals of Bangladesh Agriculture, 2022)
Motile Aeromonas septicaemia (MAS) caused by Aeromonas spp. is one of the major fish diseases that causes substantial losses in the aquaculture industry. The present study was conducted to screen the in vitro inhibitory effects of garlic extracts on Aeromonas veronii isolated from MAS, evaluate the effects of dietary inclusion of garlic extracts on growth and prevention of MAS in Labeo rohita. In vitro antibacterial activities of garlic aqueous and organic solvent extracts (ethyl acetate, methanol, ethanol, and acetone) were screened by disc diffusion assay. The minimum inhibitory concentrations (MICs) of ethyl acetate and methanol extracts were determined by using a quantitative bioassay method. Four groups of fish were fed garlic ethyl acetate extract at the rate of 0 (T1, control), 6.25 (T2), 12.50 (T3), and 25.00 (T4) mg/kg feed with three replications for 90 days. The fish fed with different concentrations of garlic extracts were artificially challenged with the high virulent A. veronii strain B55. In this study, ethyl acetate extract of garlic inhibited all the A. veronii strains (A22, B7, B9, B19, B27, B36, B55, F143, K743, and L1324) with the maximum inhibition zones. The MICs of ethyl acetate and methanol extracts were obtained 31.25 and 62.5 μg/ml, respectively. The final weight gain of L. rohita was obtained 28.21±0.51, 31.33±0.76, 40.05±0.76, and 34.82±0.51 g in the treatments T1, T2, T3, and T4, respectively. The growth of ethyl acetate extracts-fed fish were significantly (p < 0.05) higher compared to the control. The specific growth rate was also found significantly higher in the T3, T4, and T2 relative to control. The fish fed garlic extracts enriched feed at 12.5, and 25 mg/kg developed resistance against MAS, while all the control fish died with expressions of distinct disease symptoms. Therefore, garlic ethyl acetate extracts could be used for growth enhancement and prevention of MAS in L. rohita. Ann. Bangladesh Agric. (2021) 25 (1) : 11-22